STRATIFIKASI AKAD KEPEMILIKAN HARTA SEBAGAI SOLUSI PROBLEM PEMBAGIAN HARTA PASCACERAI - Indah Puspitasari; Iza Hanifuddin (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2023)
When a husband and wife are separated, either by way of divorce or one of the spouse died, one of the problems that arises is the dispute over the ownership of treasure. Because of these disputes, conflicts, quarrels, hostilities certainly occur, not even rarely to the point of having to be brought to justice. So, in this article will be presented the results of analysis related to the phenomenon and offer alternative solutions that can be used. This study uses a library research method, with a phenomenological qualitative approach. The result of the analysis is that the diversity of understanding of treasure after marriage, culture and customs in each family, makes a variety of understandings of the contract of ownership of treasure between husband and wife in society. The problems that arise are expected to be anticipated by using the contract stratification approach. For families that have no problem in harmony, the contract of ownership of treasure between husband and wife can use the usual contract, gestures, deeds and oral. For families that are considered prone to conflicts of treasure (have many assets, there are family members who are greedy with treasure, have few assets but are prone to conflict) can use a written contract. However, if you want to minimize the risk of problems or problems in the future, then the husband and wife can contract ownership of treasure through a notary or written by themselves with a stamp and signed by two male witnesses (under the hand), in accordance with QS. al-Baqarah verse 282. This is done as a precautionary step (ihktiyati). So that if unwanted things happen, the recording can be used as evidence of legally valid ownership